Ammonium perchlorate-based molecular perovskite energetic materials: preparation, characterization, and thermal catalysis performance with MoS2. Issue 2 (2nd April 2020) - Li, Xiaoxia; Hu, Shuangqi; Cao, Xiong; Hu, Lishuang; Deng, Peng; Xie, Zhaobian
ABSTRACT: In this study, ammonium perchlorate (AP)-based molecular perovskite structural high-energetic materials (H2 dabco)[NH4 (ClO4 )3 ] (DAP) were fabricated and their catalytic performance upon the addition of MoS2 nanosheets was investigated. The DAP samples were succesfully prepared via a self-assembly reaction and their morphology and structure were characterized via scanning electron microscopy, X-ray diffractometry, and Fourier transform infrared spectroscopy. The thermal decomposition performance of a pure DAP sample and of a mixture of DAP with MoS2 nanosheets were analyzed via differential scanning calorimetry. The results show that DAP has a high thermal stability at its initial decomposition temperature of 319.8°C, and that its apparent decomposition heat measures 4199 J/g. This value is higher than for AP (829.7 J/g). Furthermore, the thermal decomposition peak temperature of DAP upon the addition of 1 wt% and 3 wt% MoS2 nanosheets decreases from 394.4°C to 343.3°C and 328.8°C, respectively. The investigation of the catalysis thermal performance of DAP may foster its practical application in composite propellant.